2018
DOI: 10.22336/rjo.2018.41
|View full text |Cite
|
Sign up to set email alerts
|

Low light visual function after accelerated corneal Cross-Linking Protocols: 18 mW/cm2 vs. 9 mW/cm2

Abstract: Objective. To compare one-year results of vision, corneal aberrometry and contrast sensitivity (CS) in low light conditions between 5-and 10-minute accelerated crosslinking (CXL) protocols. Methods. Thirty eyes were evaluated in each studied group. Uncorrected (UDVA) and corrected (CDVA) distance visual acuity by the SC-2000 Snellen chart, corneal higher order aberrations using the OPD Scan III and CS using MonCv3System was tested under mesopic (20 lux) and scotopic (0.5 lux) light conditions at pre-CXL and 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Enrolled subjects were assigned to either the 18 mW/cm 2 for 5-minute protocol (30 eyes from 22 patients) or 9 mW/cm 2 for 10-minute protocol (30 eyes from 24 patients). 15…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Enrolled subjects were assigned to either the 18 mW/cm 2 for 5-minute protocol (30 eyes from 22 patients) or 9 mW/cm 2 for 10-minute protocol (30 eyes from 24 patients). 15…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have compared the effectiveness of 10- and 5-minute protocols. 12–15 However, there are currently no systematic reviews or meta-analyses comparing the outcomes of these 2 interventions. This study is the first to report these outcomes.…”
mentioning
confidence: 99%
“…The OPD scan also provides optical path difference (OPD) maps which detects total refractive error in the eye as well as the refractive error contributed by the internal structures of the eye [26]. The NIDEK OPD scan has been used to evaluate the quality of vision in patients with keratoconus after corneal transplants [27], after intracorneal ring segment implantation [28], and after accelerated corneal cross-linking [29]. Asgari et al evaluated mild and moderate keratoconus eyes after accelerated cross-linking and found that the OPD scan III had higher aberrometric repeatability in mild compared with moderate cases [30].…”
Section: Dynamic Skiascopymentioning
confidence: 99%